“On” state freezing of gait in Parkinson disease: A paradoxical levodopa-induced complication - Espay, A.J. (Lippincott Williams & Wilkins, 2012)
OBJECTIVE: To describe the phenotype of levodopa-induced “on” freezing of gait (FOG) in Parkinson disease (PD). METHODS: We present a diagnostic approach to separate “on” FOG (deterioration during the “on state”) from other FOG forms. Four patients with PD with suspected “on” FOG were examined in the “off state” (>12 hours after last medication intake), “on state” (peak effect of usual medication), and “supra-on” state (after intake of at least twice the usual dose). RESULTS: Patients showed clear “on” FOG, which worsened in a dose-dependent fashion from the “on” to the “supra-on” state. Two patients also demonstrated FOG during the “off state,” of lesser magnitude than during “on.” In addition, levodopa produced motor blocks in hand and feet movements, while other parkinsonian features improved. None of the patients had cognitive impairment or a predating “off” FOG. CONCLUSIONS: True “on” FOG exists as a rare phenotype in PD, unassociated with cognitive impairment or a predating “off” FOG. Distinguishing the different FOG subtypes requires a comprehensive motor assessment in at least 3 medication states.